Pots for Past People: Nine Roman cemeteries in the Dutch eastern river area - Reigersman-van Lidth de Jeude, W. Frédérique (Rei Cretariae Romanae Fautorum Acta, 2017)
From 2005 on the archaeological company ADC ArcheoProjecten has had the opportunity to excavate nine cemeteries of different size in the Dutch eastern river area. Two of them are still under investigation. In this article all of them will be characterised shortly. A few will get more attention in order to find an answer to questions that have risen over the past years.